The plant detectives: innovative undergraduate teaching to inspire the next generation of plant biologists - Beckmann, Elizabeth A.; Estavillo, Gonzalo M.; Mathesius, Ulrike; Djordjevic, Michael A.; Nicotra, Adrienne B. (Frontiers in Plant Science, 2015)
Encouraging more students to embrace plant science research is an urgent global priority. We have evolved a second year undergraduate course from a standard lecture/practical format into an innovative research-led learning design that gives students hands-on experience of cutting-edge plant science research and specialist instrumentation. By making tangible the links between plant genetics, biochemistry, physiology and function, the active learning curriculum extends students to their limits, and gives them insights into the multi-faceted nature of plant science research. Using genetically-mapped mutants of Arabidopsis thaliana, we challenge our students to apply their conceptual learning immediately to identify 'unknown' genetic mutations affecting plant form and function. By exposing students early in their student careers to the challenges, rigours and excitement of plant science research, we have helped them grow quickly into astute researchers who truly deserve the title 'Plant Detectives'. Many have become motivated to continue their studies as plant biologists in research-focused honours (pre-doctoral) and doctoral programs.